Model Kurikulum Ramah Anak Beriorentasi Anti Bullying di Mts Dakwah Islamiyah Putra Ponpes Nurul Hakim Lombok Barat - Isnaini, Isnaini; Syahri, Akhmad; Musta’in, Musta’in (Jurnal Ragam Pengabdian, 2026)
This study aims to describe a child-friendly curriculum model oriented toward anti-bullying at MTs Dakwah Islamiyah Putra, Nurul Hakim Islamic Boarding School, West Lombok. This study used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The research subjects included teachers and students. Data analysis used the Miles and Huberman model. The results show that Nurul Hakim Islamic Boarding School does not yet have a written child-friendly curriculum, but child-friendly educational principles have been implemented through a hidden curriculum within the boarding school culture and the daily lives of students. This implementation is evident through character education based on Islamic values, a humanistic parenting system, a child-friendly boarding school program, anti-bullying educational media, and a comfortable eco-boarding school environment. The dominant form of bullying found was verbal bullying through excessive joking between friends. Preventive efforts are carried out through character development, counseling, dormitory supervision, and regular anti-bullying outreach. This study concludes that the child-friendly curriculum model oriented toward anti-bullying at Nurul Hakim Islamic Boarding School is implemented through a religious, humanistic, and child-protection-based educational culture and has the potential to become a reference for other Islamic boarding schools.